Avoiding Taxes: Banks' Use of Internal Debt - Franz Reiter; Dominika Langenmayr; Svea Holtmann (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper investigates how multinational banks use internal debt to shift profits to low-taxed affiliates. Using regulatory data on multinational banks headquartered in Germany, we show that banks use this tax avoidance channel more aggressively than non-financial multinationals do. We find that a ten percentage points higher corporate tax rate increases the internal net debt ratio by 5.7 percentage points, corresponding to a 20% increase at the mean. Our study also takes into account the existence of conduit entities, which simply pass through financial flows. If conduit entities are systematically located in low-tax countries, previous studies may have underestimated the extent of debt shifting.
Keywords: H25; G21; F23; 330; profit shifting; internal debt; multinational banks; taxation